2013
DOI: 10.1016/j.cca.2013.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between adiponectin and nitrite in healthy and preeclampsia pregnancies

Abstract: Our findings showed higher levels of adiponectin and lower nitrite levels in PE compared to HP, and these levels were positively correlated in HP and in PE presenting lower concentrations of ADMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Taken together, these results show that the combined administration of nitrite and sildenafil is not advantageous compared with sildenafil alone, because sildenafil alone protected against hypertension and fetal growth restriction without increase cGMP levels in HP + S group, thus, suggesting that sildenafil effects in hypertension in pregnancy were not dependent of NO and cGMP. Thereby, our present results provide preclinical evidences to support the use of sildenafil in women with hypertension-in-pregnancy with features of preeclampsia (Trapani et al, 2016), even though preeclamptic women have shown reduced NO formation compared to healthy pregnant women (Ehsanipoor et al, 2013;Eleuterio et al, 2013;Schiessl et al, 2006;Tranquilli et al, 2004;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 59%
“…Taken together, these results show that the combined administration of nitrite and sildenafil is not advantageous compared with sildenafil alone, because sildenafil alone protected against hypertension and fetal growth restriction without increase cGMP levels in HP + S group, thus, suggesting that sildenafil effects in hypertension in pregnancy were not dependent of NO and cGMP. Thereby, our present results provide preclinical evidences to support the use of sildenafil in women with hypertension-in-pregnancy with features of preeclampsia (Trapani et al, 2016), even though preeclamptic women have shown reduced NO formation compared to healthy pregnant women (Ehsanipoor et al, 2013;Eleuterio et al, 2013;Schiessl et al, 2006;Tranquilli et al, 2004;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 59%
“…A reduction in endogenous nitric oxide (NO) bioavailability in hypertensive pregnancy is supported by several studies and interactions between H 2 S and NO have been described before . Indeed, a previous study from our group suggested H 2 S and NO interaction in hypertension‐in‐pregnancy, thus, we aimed to investigate the antihypertensive effects and changes in feto‐placental parameters exerted by NaHS in hypertension‐in‐pregnancy.…”
Section: Introductionmentioning
confidence: 79%
“…NO is required vascular alterations during normal pregnancy to support the increased blood volume [28]. NO deficiency has been shown to impair the vasorelaxation in human and animal models of PE [2931] and increased NO bioavailability could contribute to improve maternal and fetal outcomes.…”
Section: Endothelial Dysfunction Is a Common Thread That Could Contrimentioning
confidence: 99%